Wireless Animatronic Hand - Hariharan, A.; Hariharan, P.; Dinesh, V.; Kumar, R. Deleep; Jeyanthi, J.E. (International Journal of Membrane Science and Technology, 2023)
As a result of employees utilizing their bare hands, there are more accidents in industries every year. Animatronic hands resemble human hands and are capable of carrying out a variety of tasks that humans are unable to do. Human hands cannot readily finish difficult tasks, but animatronic hands can mimic human movements and complete them. A number of actuators and sensors make up the robotic hand, which are managed by a person's hand. The pushers control how far the fingers can move. We employ flex sensors to detect the positions. The positions and motion of the hand are reported by sensors to Arduino. The microcontroller uses a 433MHz transmitter and receiver in both transmitter and receiver side to used for transmitting the data, so it will be access in remote area. We employ servo motors as actuators by getting the position and motion from another microcontroller also attached. Two microcontrollers are interconnected with 433MHz transmitter and receiver, Transmitter and receiver for 433 MHz When sending and receiving radio signals between any two devices, RF refers to a set of electronic RF transmitters and receiver modules. The transmitter module at the transmitter end transmits the data, which the receiver module at the receiver end receives.